Strain engineering of SnS2/PtS2 layered heterojunction photocatalysts for landscape environmental remediation: theoretical calculations - Zou, Yihan; Abd-Ghafar, Azmiah; Abdul Rashid, Suhaila; Mohd Firdaus, Rohana; Jiang, Anqi (Elsevier B.V., 2025)
Heterojunction photocatalysts have emerged as a promising approach for the remediation of environmental pollutants. In this investigation, SnS2 monolayer and PtS2 monolayer were employed to construct heterojunctions (SnS2/PtS2, SnS2/PtS2/SnS2, and PtS2/SnS2/PtS2). First-principles calculations were conducted to comprehensively analyze their structural stability, electronic properties, interlayer charge transfer mechanisms, and optical behavior. The results demonstrate that all examined heterojunctions possess robust structural stability. The indirect band gaps of these heterostructures range between 1.561 eV and 1.688 eV, exhibiting characteristic type-II band alignment. Optical analyses indicate that the SnS2/PtS2/SnS2 heterojunction achieves superior light absorption efficiency within the visible spectrum. Furthermore, this heterojunction displays the lowest overpotential, indicative of enhanced photocatalytic water-splitting capabilities. These insights offer valuable guidance for the rational design of heterojunction photocatalysts.